2018
DOI: 10.1371/journal.pone.0204091
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of short message services and voice call interventions for antiretroviral therapy adherence and other outcomes: A systematic review and meta-analysis

Abstract: BackgroundThe potential of using mobile phone technologies to improve antiretroviral therapy (ART) adherence has provided a new facet to human immunodeficiency virus (HIV) research. The quality of evidence and the strength of recommendations of existing reviews, however, do not adequately support large-scale adoption of the intervention. This review adopted broad selection criteria to include all mobile phone-based interventions designed to improve patient’s adherence to ART.MethodsWe performed a systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 50 publications
0
70
2
2
Order By: Relevance
“…It is important to note that our review excluded eHealth interventions that use only SMS or voice messaging. A recent systematic review of SMS and voice call interventions for HIV‐positive subjects found that a majority were for individuals in low‐ and middle‐income countries, contrasting the findings of this review . Limited access to new technologies in these settings has likely discouraged researchers from developing interventions that utilize these platforms.…”
Section: Resultscontrasting
confidence: 66%
“…It is important to note that our review excluded eHealth interventions that use only SMS or voice messaging. A recent systematic review of SMS and voice call interventions for HIV‐positive subjects found that a majority were for individuals in low‐ and middle‐income countries, contrasting the findings of this review . Limited access to new technologies in these settings has likely discouraged researchers from developing interventions that utilize these platforms.…”
Section: Resultscontrasting
confidence: 66%
“…between individual studies based on the cutoff value [28]. Similar systematic reviews showed that text-messaging interventions were effective for self-management of diabetes, weight loss, smoking cessation, physical activities and medication adherence for antiretroviral therapy [58,59]. In the current review, the effect size was low as compared to evidences on ART.…”
Section: Discussionmentioning
confidence: 73%
“…The meta-analysis has shown that phone messaging group had a modest increment in treatment success rate compared to standard care (RR 1.04, 95% CI 1.02 to 1.06) with low heterogeneity (I 2 = 7%, p < 0.0002) between individual studies based on the cutoff value [28]. Similar systematic reviews showed that text-messaging interventions were effective for self-management of diabetes, weight loss, smoking cessation, physical activities and medication adherence for antiretroviral therapy [58,59]. In the current review, the effect size was low as compared to evidence on ART.…”
Section: Discussionmentioning
confidence: 99%
“…The subgroup Interventions An interactive (two way) text-based medication and appointment reminder, and educational messages using a total of 8 SMSs per 2 weeks for two months Outcomes After 8 weeks intervention, successful completion of treatment was 93% in intervention and 89% in control analysis has shown that two-way phone messaging interventions have a small effect on TB treatment success as compared with one-way messaging. Evidence also indicated that SMS interventions for ART that run two-way SMS communication were more acceptable than non-interactive reminders [59]. An interactive communication could provide an opportunity for patients to get their voices heard, and improve relationships and enhance engagement in their treatment.…”
Section: Discussionmentioning
confidence: 99%